Why Jesus appears to people today a Biblical understanding - Bond, Mel. (Shippensburg : Destiny Image, Inc., 2012)
Seeing is believing… Do you question whether Jesus truly appears to people today? Do you long to see Him for yourself? Why Jesus Appears to People is an intimate, modern-day account of the author’s personal experiences seeing Jesus. It is also an introduction into a lifestyle that positions you for the same encounters. But Jesus came and touched them and said, “Arise, and do not be afraid.” When they had lifted up their eyes, they saw no one but Jesus only (Matthew 17:7-8). Being saturated in the Word of God is a gateway into supernatural visitations with Jesus, both.
Dedication; Contents; Foreword; Preface; Chapter 1 Why Jesus Appears to People; Chapter 2 Four Different Kinds of Visions; Chapter 3 The Dispensation of Visions; Chapter 4 God's Unconditional Love in the Last Days; Chapter 5 Understanding Warfare; Chapter 6 Guarding Your Mind; Chapter 7 Humility Before Honor; Chapter 8 Seeing With Your Spiritual Eyes; Chapter 9 Pray With Your Whole Heart; Chapter 10 Mansion in Glory; Chapter 11 The Importance of Your Life; Chapter 12 Jesus, the Horn of Salvation; Chapter 13 Jesus Wants to Appear to You!; Chapter 14 Testimonies of Jesus Appearing
Description based upon print version of record.
Chapter 15 Galatians 1:8
Keywords: Jesus Christ -- Apparitions and miracles; Visions; Private revelations; Jesus Christ -- Person and offices; Spiritual life -- Christianity; RELIGION / Biblical Studies / Old Testament; RELIGION / Judaism / Sacred Writings; Electronic books; Electronic books